The impact of pollution on the mental health of the population (Journal of Medical Science, 2018)
This paper analyzes the relationship between pollution of the natural environment and the population’s mental health, based on the example of three urban agglomerations: Gdańsk, Poznań, and Katowice. The following factors were analyzed: air quality, the quality of water from the municipal waterworks, data concerning social pathologies, number of private psychological, psychotherapeutic, and psychiatric practices, as well as statistics concerning psychiatric healthcare in the Pomeranian, Greater Poland, and Silesian voivodships in 2011. Based on the collected data, presented in a descriptive manner, a hypothesis was drawn that natural environment pollutions may influence the mental health of the population. This conclusion was drawn from the fact that worse air quality in Katowice correlates to a higher percentage of social pathologies and a higher demand for psychiatric healthcare than in Poznań or Gdańsk.